2018
DOI: 10.1308/rcsann.2018.0085
|View full text |Cite
|
Sign up to set email alerts
|

An innovative way of managing coeliac artery stenosis during pancreaticoduodenectomy

Abstract: Coeliac artery stenosis (CAS) is rarely of consequence owing to rich collateral supply from the superior mesenteric artery via the pancreatic head. Pancreaticoduodenectomy (PD) in CAS disrupts these collaterals, and places the liver, stomach and spleen at risk of ischaemia. A 56-year-old man presented with a 3-week history of obstructive jaundice. Computed tomography revealed an operable periampullary tumour with CAS due to compression by the median arcuate ligament with multiple collaterals in the pancreatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…First, it requires a high level of skill for stenting in the case of MAL compression. There are previous reports of failure in cases of stenting[ 21 - 23 ]. It is hoped that IVR techniques will become more widespread and improve in the future.…”
Section: Discussionmentioning
confidence: 99%
“…First, it requires a high level of skill for stenting in the case of MAL compression. There are previous reports of failure in cases of stenting[ 21 - 23 ]. It is hoped that IVR techniques will become more widespread and improve in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Two groups chose to perform stenting prior to PD to ensure adequate flow of the celiac trunk without dividing MAL [53,54]. Balakrishnan et al reported an unsuccessful attempt at upfront endovascular stenting of the celiac trunk prior to PD, leading the patient to undergo subsequent MAL release and arterial reconstruction [55]. Endovascular intervention during neoadjuvant chemotherapy has been described in another case study [10].…”
Section: Management Of Median Arcuate Ligament Syndrome and Our Exper...mentioning
confidence: 99%
“…Resection of pancreatic head cancer routinely involves the sacrifice of these communications, which may lead to insufficient perfusion of the upper abdominal organs and sometimes (e.g.,in the case of significant CAS) to their ischemic complications. To prevent these dramatic complications, the GDA clamping test has already been described as a mandatory test to evaluate the hepatic blood flow by ascertaining the satisfactory pulsation of the proper hepatic artery, as well as via Doppler ultrasonography [ 10 , 11 , 12 , 13 ]. To the best of our knowledge, there are no quantitative data or well-established algorithms to assess the perfusion of upper abdominal organs and hepatic blood flow during pancreatic surgery before and after GDA clamping.…”
Section: Introductionmentioning
confidence: 99%